Atomic arrangements in an amorphous CoFeB ribbon extracted via an analysis of radial distribution functions. (23rd July 2021) - Pussi, K; Barbiellini, B; Ohara, K; Yamada, H; Dwivedi, J; Bansil, A; Gupta, A; Kamali, S
Abstract: We discuss the atomic structure of amorphous ferromagnetic FeCoB alloys, which are used widely in spintronics applications. Specifically, we obtain the pair-distribution functions for various atomic pairs based on high-energy x-ray diffraction data taken from an amorphous Co20 Fe61 B19 specimen. We start our reverse Monte Carlo cycles to determine the disordered structure with a two-phase model in which a small amount of cobalt is mixed with Fe23 B6 as a second phase. The structure of the alloy is found to be heterogeneous, where the boron atoms drive disorder through the random occupation of the atomic network. Our analysis also indicates the presence of small cobalt clusters that are embedded in the iron matrix and percolating the latter throughout the structure. This morphology can explain the enhanced spin polarization observed in amorphous magnetic materials.